Characterization and Evaluation of Different Cultivars of Sapota (Manilkara achras L.) under the Gangetic Plain of West Bengal - Mondal, Tanmoy; Mahata, Subrata; Bauri, Fatik Kumar; Mandi, Gouri; Mishra, Dilip Kumar (International Journal of Bio-resource and Stress Management, 2023)
The present experiment was carried out in Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal during April to June of 2022 to find out the best cultivars of this region. The experiment was laid out in Randomized Block Design (RBD) with seven treatments each replicated thrice. The ten years old seven cultivars (Cricket Ball, PKM-1, PKM-2, PKM-3, CO-1, CO-2 and CO-3) are planted in a square system in a spacing of 5×5 m2. The maximum fruit weight was found in CO-1 (73.86 g) and followed by CO-2 (73.53 g). The longest fruit length and dimension were observed from CO-2 (7.00 cm and 5.07 cm respectively). The maximum pulp contains in the cultivar is CO-2 (69.58 g) followed by CO-1 (68.96 g). The maximum value of TSS was found in CO-2 (25.17 oBrix) followed by Cricket Ball (21.22 oBrix) and CO-3 (20.28 oBrix). The lowest acidity was recorded in CO-2 (0.12%) followed by CO-3 (0.16%) and CO-1 (0.20%). The cultivar CO-2 registered the highest values of ascorbic acid (62.85 mg 100 g-1), total sugar (16.78%), non-reducing sugar (6.44%) and TSS: acid ratio (209.72). It can be concluded that CO-2 appeared to be the best variety based on the fruit’s physical and quality attributes. As this experiment was carried out based on a limited number of varieties, more research was required on the existing germplasm of India. That might be supported in sapota’s future production, processing, and marketing.